2019
DOI: 10.3389/fncel.2019.00211
|View full text |Cite
|
Sign up to set email alerts
|

Necrostatin-1 Ameliorates Peripheral Nerve Injury-Induced Neuropathic Pain by Inhibiting the RIP1/RIP3 Pathway

Abstract: Necrostatin-1 is an inhibitor of necroptosis, a form of programmed cell death that has been reported to be involved in various neurological diseases. Presently, the role of necroptosis in neuropathic pain induced by peripheral nerve injury is still unclear. This study was focused on investigating the potential effects of necroptosis in the development and progression of neuropathic pain in a rat model and the possible neuroprotective effects of necrostatin-1 in neuropathic pain. The results indicated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 58 publications
(71 reference statements)
2
27
0
Order By: Relevance
“…This observation is consistent with other studies showing that chronic inhibition of RIPK1 can lead to reduced expression of RIPK3 and/or MLKL in different inflammatory rodent models [26][27][28][29]. Inhibiting the kinase activity of RIPK1 may result in an increase stability of RIPK1.…”
Section: Discussionsupporting
confidence: 92%
“…This observation is consistent with other studies showing that chronic inhibition of RIPK1 can lead to reduced expression of RIPK3 and/or MLKL in different inflammatory rodent models [26][27][28][29]. Inhibiting the kinase activity of RIPK1 may result in an increase stability of RIPK1.…”
Section: Discussionsupporting
confidence: 92%
“…Western blot was performed on the proteins p-RIPK3 and p-MLKL in PRU-treated cells upon co-treatment with inhibitor Nec-1 at 0.1 mM concentration. Nec-1 is a small effective molecule that inhibits the process of necroptosis by causing reduction in RIPK1/RIPK3 kinase activity leading to the inhibition of several residues of serine-phosphorylation during the formation of the necrosome complex [ 35 , 39 ]. The results as depicted in Figure 5 b show that the elevated expression of p-RIPK3 and p-MLKL in the PRU treated cells were found to be reduced upon co-treatment with the inhibitor Nec-1.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we next sought to attenuate fat graft fibrosis in vivo by reducing necroptotic death of MFCs and demonstrated that Nec-1 treatment reduced fat graft fibrosis. Studies of necroptosis have shown that intraperitoneal injection of Nec-1 protects cellular structures under necroptosis-related pathological conditions in animal models ( Liang et al, 2019 ). This is the first report of the long-term therapeutic application of Nec-1 to reduce fat graft fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the effects of necroptosis inhibition in vivo , fat-grafted mice were intravenously injected with 1.65 mg/kg necrostatin-1 (Nec-1; Sigma-Aldrich, St. Louis, MO, United States; Linkermann et al, 2013 ; Caccamo et al, 2017 ; Liang et al, 2019 ) once per day for 30 days from the fourth week after grafting. Control fat-grafted mice were intravenously injected with the same volume of DMSO diluted in saline solution.…”
Section: Methodsmentioning
confidence: 99%